2011
DOI: 10.5402/2011/854924
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Maxillary Deficiency by Miniplates: A Case Report

Abstract: Introduction. Numerous devices have been introduced for correction of Class III malocclusion and maxillary deficiency. Aim. To assess the dentoskeletal effects of miniplates combined with Class III traction in treating Cl III malocclusion and maxillary deficiency in growing patients. Methods. This case describes the treatment of a maxillary-deficient 11-year-old boy by using miniplates. The patient's parents rejected the use of extraoral appliances and major surgical correction; therefore the treatment was don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Tongue plate has been used for correction of maxillary deficiency [27]. Mechanism of tongue plate [7] is very similar to the tongue appliance. The pressure of tongue during rest position and swallowing is transmitted through the tongue plate to the deficient maxilla.…”
Section: During Mixed Dentitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tongue plate has been used for correction of maxillary deficiency [27]. Mechanism of tongue plate [7] is very similar to the tongue appliance. The pressure of tongue during rest position and swallowing is transmitted through the tongue plate to the deficient maxilla.…”
Section: During Mixed Dentitionmentioning
confidence: 99%
“…Maxillary deficiency is a common feature of cleft lip and palate patients due to scar tissue of the lip and palate closure. For treatment of maxillary deficiency, various devices, such as facemask [2], protraction headgear [3], orthopedic mask [4], reverse chin cup [5], tongue appliance [6], tongue plate [7], surgically assisted orthopedic protraction, and distraction osteogenesis have been introduced [8]. Treatment of cleft lip and palate in patients should be started after birth and continues to adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…(4,10) The resting tongue pressure and also the pressure produced during swallowing are transmitted to the nasomaxillary complex via this device and exert a forward push force on the maxilla without directly affecting the mandible. (12)(13)(14)(15)(16)(17) To date, no study has evaluated the effects of tongue plate on patients with cleft lip and cleft palate. Therefore, the aim of the present study was to evaluate the effects of tongue plate on the nasomaxillary complex of patients with unilateral cleft lip and cleft palate.…”
Section: Introductionmentioning
confidence: 99%
“…It was also suggested that intentionally ankylosed teeth may be used as abutments for extraoral traction in patients with a severe disturbance in maxillary growth [10]. Miniscrew implants and miniplates have also been used to provide the necessary orthodontic anchorage in these cases [11][12][13][14]. The tongue plate and tongue appliance have also been used for the correction of maxillary deficiency in growing patients [15][16][17].…”
Section: Introductionmentioning
confidence: 99%